Review of documentary film: new forms and possibilities - Nurshaikhova, A.A.; Negizbayeva, M.O.; Imanova, A.S. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
This article delves into the realm of documentary journalism in contemporary society and its consequential effect on social opinion. It expounds upon novel prospects and opportunities for the evolution of documentary investigations. By providing a comprehensive overview of the development of documentaries and projects in Kazakhstan, this article demonstrates the magnitude of their significance in the sphere of social life. The primary aim of this study is to examine in detail the progress of documentary filmmaking and its impact on public opinion. The significance of documentary investigations in disseminating information and raising social and political issues is also explored. Furthermore, the technological accessibility and distribution of films in modern society are analyzed. Through a thorough analysis of the subject matter, the problems are identified, and feasible solutions are presented, highlighting the role of documentaries in raising pertinent social issues.